Modulation of HLA-DR in dry eye patients following 30 days of treatment with a lubricant eyedrop solution - Fernandez KB (Dove Medical Press, 2015)
Karen B Fernandez, Seth P Epstein, Geoffrey S Raynor, Alan T Sheyman, Morgan L Massingale, Peter G Dentone, Lukas D Landegger, Penny A Asbell Department of Ophthalmology, Mount Sinai School of Medicine, New York, NY, USA Purpose: To determine the changes in dry eye disease (DED) severity and the percentage of cells expressing HLA-DR on the ocular surface following treatment with lubricant eyedrops containing polyethylene glycol and propylene glycol (PEG/PG) and the gelling agent hydroxypropyl guar (HP-Guar).Patients and methods: Nineteen patients with DED used PEG/PG + HP-Guar eyedrops four times per day for 30 days. Assessments included DED severity (Ocular Surface Disease Index [OSDI], corneal staining, conjunctival staining, tear film break-up time [TFBUT], and Schirmer testing) and impression cytology of the conjunctiva with masked flow cytometry at baseline and at 30 days.Results: There was a significant decrease in corneal staining (P<0.01), OSDI (P=0.02), and TFBUT (P<0.01) following treatment with PEG/PG + HP-Guar. Results from flow cytometry revealed a significant decrease in cells expressing HLA-DR (P=0.02).Conclusion: Treatment with PEG/PG + HP-Guar eyedrops showed improvement in dry eye severity and reduction in surface inflammation as indicated by a reduction in HLA-DR expression. Keywords: artificial tears, dry eye disease, hydroxypropyl guar, inflammation, lubricating eyedrops, polyethylene glycol, propylene glycol